Jurassic Source Rock Characteristics and Resource Evaluation in Junggar Basin - Zhou, Yongshen; Fu, Aihua; Zhao, Xiaojie (International Journal of Natural Resources and Environmental Studies, 2024)
Junggar Basin is one of the important petroliferous basins in China. Based on sedimentology, palaeogeography, geochemical characteristics, tectonic thermal evolution and other aspects, this study analyzes the characteristics and distribution law of source rocks, and predicts the total oil and gas resources of Jurassic in the basin. Middle and Lower Jurassic is the main hydrocarbon source rock strata of Jurassic, and a large set of thick coal and dark mudstone are developed on delta, shore-shallow lake and deep lake facies in the basin, among which Badaowan Formation is 200 800 m thick; Xishanyao Formation is 50m 550m thick, which has great development prospect, but there are few exploration results at present. Through geochemical index analysis and thermal evolution simulation of source rocks, the middle and lower Jurassic source rocks are mostly medium-good source rocks, and the distribution and thermal evolution degree of mature source rocks in the south and east of the basin are higher than those in the north and west of the basin, so they have the conditions for mass production of hydrocarbons.